2014
DOI: 10.1161/circresaha.114.303915
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Long Noncoding RNA, LIPCAR, Predicts Survival in Patients With Heart Failure

Abstract: Objective: To study the role of long noncoding RNAs as potential biomarkers in heart disease. Methods and Results: Global transcriptomic analyses were done in plasma RNA from patients with or without left ventricular remodeling after myocardial infarction. Regulated candidates were validated in 3 independent patient cohorts developing cardiac remodeling and heart failure (788 patients). The mitochondrial long noncoding RNA uc022bqs.1 (LIPCAR) was downregulated early after myocardial infarction but upregulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
461
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 567 publications
(477 citation statements)
references
References 19 publications
12
461
0
4
Order By: Relevance
“…Interestingly, another recent study identified a novel circulating lncRNA, LIPCAR, as a molecular marker for HF. 32 Our study, together with these prior reports, indicates that lncRNAs are a novel class of regulators and biomarkers for cardiovascular biology and diseases.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, another recent study identified a novel circulating lncRNA, LIPCAR, as a molecular marker for HF. 32 Our study, together with these prior reports, indicates that lncRNAs are a novel class of regulators and biomarkers for cardiovascular biology and diseases.…”
Section: Discussionsupporting
confidence: 64%
“…This review also describes the finding of mitochondrial lncRNAs in different cell types such as HeLa cells, breast cells and ventricular tissue [34,35,36], fulfilling different roles as regulators of translation or as novel biomarkers of disease progression. Among these, LIPCAR (Long Intergenic noncoding RNA Predicting CARdiac remodeling) is worthy of mention, as it is upregulated at late stages of left ventricular remodeling and is elevated in patients with chronic heart failure, suggesting this mtlncRNA as a prognostic indicator for cardiovascular mortality [37].…”
Section: Discussionmentioning
confidence: 99%
“…S1) were shown to contribute to muscle or myocardial function (8, 9). miRNAs and other classes of RNA have been profiled in failing human myocardium (10)(11)(12)(13)(14)(15)(16)(17), and a selected subset was also investigated as circulating biomarkers in HF (18)(19)(20)(21)(22)(23)(24). However, in these studies heart tissue and circulating miRNA abundance changes were not acquired simultaneously to correlate changes in tissue versus circulating miRNA composition.…”
mentioning
confidence: 99%